Comparison of the Proteomes of Porcine Macrophages and a Stable Porcine Cell Line after Infection with African Swine Fever Virus - Elisabeth Wöhnke (MDPI AG, 2021)
African swine fever virus (ASFV), causing an OIE-notifiable viral disease of swine, is spreading over the Eurasian continent and threatening the global pig industry. Here, we conducted the first proteome analysis of ASFV-infected primary porcine monocyte-derived macrophages (moMΦ). In parallel to moMΦ isolated from different pigs, the stable porcine cell line WSL-R was infected with a recombinant of ASFV genotype IX strain “Kenya1033”. The outcome of the infections was compared via quantitative mass spectrometry (MS)-based proteome analysis. Major differences with respect to the expression of viral proteins or the host cell response were not observed. However, cell-specific expression of some individual viral proteins did occur. The observed modulations of the host proteome were mainly related to cell characteristics and function. Overall, we conclude that both infection models are suitable for use in the study of ASFV infection in vitro.